A case report of incidental finding of compound odontoma on a panoramic radiograph - Agung, Anak Agung Gde Dananjaya; Laurentina, Made; Janadewi, I Gusti Agung; Sukmadewi, Putri Marina; Epsilawati, Lusi (Ikatan Radiologi Kedokteran Gigi Indonesia, 2023)
Objectives: The purpose of this case study was to report the compound odontoma’s founding in a panoramic radiograph. Case Report: An 11-year-old female patient came with her parents to the pedodontics of Dental Hospital Padjadjaran Bandung with the chief complaint of a palatal bite with an unerupted left maxillary posterior tooth. Then the patient took the panoramic and cephalometry radiographs to confirm the diagnosis. The result from the panoramic radiograph was that there were multiple radioopaques with a tooth-like structure contained, surrounded by a radiolucent band, and the lesion had a corticated, well-defined border. Radiodiagnosis has been established as a compound odontoma associated with an unerupted maxillary second premolar. Conclusion: Compound odontoma is a benign tumor that often occurs at the age of tooth development and often causes delayed tooth eruption. Panoramic radiographs as radiographic aids play a very important role in identifying these tumors.